Quantitative assessment of the financial materiality of climate physical risks: A case study - Lucia Alessi; Andrea Giacomelli (European Commission, 2024)
We offer an applied approach to the double materiality assessment of environmental, social and governance (ESG) matters, which could serve as practical guidance to the 60K companies required by EU regulation (CSRD) to carry out this assessment. Focussing on the financial materiality of climate physical risks, due to its regulatory priority, we provide numerical examples, developed in compliance with all relevant regulatory requirements (ESRS). These examples are based on a generalised methodology, which allows to perform both impact and financial materiality assessments on any sustainability matter, adopting the most suitable sources of information: publicly available scientific data to perform fully transparent ESG risk estimates and expert judgment (of firm managers and/or advisors) to consider the significant idiosyncratic features characterising the financial effects of ESG matters.
Keywords: D81; G32; K32; Q51; Q54; Q56; 330; Sustainability reporting standards; double materiality assessment; ESG sustainability report; environmental sustainability; ESG risk management; climate physical risk; idiosyncratic forward-looking information